2022
DOI: 10.1101/2022.01.28.22269743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 self-testing in Nigeria: Stakeholders’ opinions and perspective on its value for case detection

Abstract: Background COVID-19 testing coverage is limited in Nigeria. Access to SARS-CoV-2 self-testing kits may help improve the detection of asymptomatic and mildly symptomatic cases and increase the currently low rate of COVID-19 testing in the country. Before implementing SARS-CoV-2 self-testing in Nigeria, it is imperative to assess the populations perceptions regarding this innovation. We therefore conducted a qualitative study to investigate peoples values and preferences for SARS-CoV-2 self-testing in Nigeria. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 26 publications
5
23
0
Order By: Relevance
“…In our inquiry, acceptability was conceptualized as a composite of the public's values toward self-testing, including agreement with the concept of self-testing (73.91% and 60.09% of female and male respondents were in agreement, respectively); willingness to pay for self-testing (mean of 5.64 USD (SD 4.73) for the 69% of respondents who would pay for a self-test device); willingness to serially self-test (44.57% of females and 39.48% of males expressed a willingness to perform weekly self-tests if they were provided free of charge and recommended by health authorities); and likelihood to use self-testing (12.95% and 36.21% of respondents were "very likely" or "likely", respectively, to use a self-test when needed). Although satisfactory, the rates of likelihood to use a self-test were not as high as those found in Indonesia [26] or Nigeria [27], other countries where surveys of people's values and attitudes in relation to self-testing have been conducted using the same methodology as used for the survey presented here.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In our inquiry, acceptability was conceptualized as a composite of the public's values toward self-testing, including agreement with the concept of self-testing (73.91% and 60.09% of female and male respondents were in agreement, respectively); willingness to pay for self-testing (mean of 5.64 USD (SD 4.73) for the 69% of respondents who would pay for a self-test device); willingness to serially self-test (44.57% of females and 39.48% of males expressed a willingness to perform weekly self-tests if they were provided free of charge and recommended by health authorities); and likelihood to use self-testing (12.95% and 36.21% of respondents were "very likely" or "likely", respectively, to use a self-test when needed). Although satisfactory, the rates of likelihood to use a self-test were not as high as those found in Indonesia [26] or Nigeria [27], other countries where surveys of people's values and attitudes in relation to self-testing have been conducted using the same methodology as used for the survey presented here.…”
Section: Discussionmentioning
confidence: 72%
“…If social safety nets are not provided, self-isolation and reporting of a COVID-19 infection might be neither feasible nor desirable for affected people. As other self-testing studies in Indonesia and Nigeria have suggested, self-isolation might only be guaranteed if there are provisions in place to ensure that those who use a self-test do not lose their job or social position[26,27].…”
mentioning
confidence: 99%
“…8,9,17,18 However, there were concerns with the ability of LMICs to rapidly scale up the detection of SARS-CoV-2 using real-time reverse transcription polymerase chain reaction (RT-PCR) testing with often few fully equipped laboratories in the early stages of the pandemic, available resources to purchase reagents as well as potential stock-outs of reagents. [19][20][21] In addition, concerns among the public, especially in LMICs, about accessing RT-PCR testing facilities, especially if this involves interacting with patients with COVID-19, potentially travelling long distances to access testing sites with associated time and cost implications and conflicts with work schedules, as well as a lack of privacy. [22][23][24] The concept of self-testing with rapid, lateral flow, SARS-CoV-2 antigen detection tests (RADT) helps to address these concerns, 13,19,[22][23][24] building on existing strategies for patients with diabetes as well as those with HIV, hepatitis C, malaria, and syphilis, testing themselves at home.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] In addition, concerns among the public, especially in LMICs, about accessing RT-PCR testing facilities, especially if this involves interacting with patients with COVID-19, potentially travelling long distances to access testing sites with associated time and cost implications and conflicts with work schedules, as well as a lack of privacy. [22][23][24] The concept of self-testing with rapid, lateral flow, SARS-CoV-2 antigen detection tests (RADT) helps to address these concerns, 13,19,[22][23][24] building on existing strategies for patients with diabetes as well as those with HIV, hepatitis C, malaria, and syphilis, testing themselves at home. 13,19,[25][26][27][28][29][30] The benefits of self-testing at home included greater uptake, ability to test at scale, efficiency with for instance no additional staff and personal protective equipment (PPE) involved, increased privacy reducing the potential for possible stigma, lack of contact with possible patients with COVID-19 in healthcare facilities as well as convenience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation